Effects of Multi-modal Therapeutic Approach in Cervical Radiculopathy - Shaheen, Farah; Bashir, Muhammad Salman; Anwar, Naveed; Manzoor, Nosheen; Khalid, Kehkshan; Tauqeer, Sana (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the effect of Mechanical cervical traction and Laser therapy along with isometric neck exercises in cervical radiculopathy patients. Study Design: Quasi-experimental study. Place and Duration of Study: Kannan Physiotherapy and Spine Clinic, Lahore Pakistan, from Jul to Dec 2020. Methodology: The study included cervical radiculopathy patients with symptoms for over two weeks. The diagnosis was confirmed by the orthopaedic department. The subjects were allocated to two equal groups by lottery method. Group-A Received Laser therapy with isometric neck exercises, and Group-B received mechanical traction with isometric neck exercises. The neck disability index, numeric pain rating scale and patient-specific function scale were used to collect data, which was analyzed using SPSS-22. Results: Out of the 128 patients, 64(50%) were in each of the two groups. The overall mean age was 41.95±36.50years, and 76(59.4%) participants were male. After three weeks of treatment sessions, statistically significant improvement was found in decreasing pain within group B having mechanical traction along isometric neck exercises (p<0.05). Conclusion: Our study concluded that both treatment techniques, Laser therapy with isometric neck exercises and mechanical traction with isometric neck exercises, effectively decreased pain; however, mechanical traction with isometric neck exercises was superior.